Use of mobile phones by subsistence farmers in the Kingdom of Eswatini: a design science research - Vilakazi, Mlungisi Bongani Lehlohonolo (Department of Information Systems, 2021)
Access to information is one of the key ways of assisting farmers to improve their agricultural output, gain access to markets and generate income. Governments, NGOs, Universities and other institutions have volumes of information that can benefit farmers, but lack the means to timeously and easily share this information with the farmers. There exists a large gulf between those that need information and the entities that possess information, and bridging this gap is crucial. The advancement of mobile phones and their high adoption levels by developing countries makes them one of the most ideal means of disseminating information amongst farmers. The use of mobile phones by farmers not only benefits farmers, but also the organizations supporting them by improving the means of communication. This research looks at the effects mobile phone communications has on farmers and the organisations supporting farmers. The use of mobile phones enhances means of communications, improves internal processes within organisations and also ameliorates means of engagement with farmers. This study follows the Design Science Research approach to develop a communications module for a project working with smallholder farmers in Eswatini. The developed artefact is designed to benefit both parties, the farmers receiving the information and the organisations supporting them, the content creators.